Blow Fly - Cornwell, Patricia Daniels (New York : G. P. Putnam's Sons, 2003)
Leaving Virginia in search of peace and quiet, Dr. Kay Scarpetta journeys to Florida, where a series of baffling murders entangles her in an international conspiracy that confronts her with the most unexpected circumstance of her life.
"A Scarpetta novel"--Jkt.
Keywords: Scarpetta, Kay (Fictitious character) -- Fiction; Medical examiners (Law) -- Fiction; Forensic pathologists -- Fiction; Women physicians -- Fiction; Richmond (Va.) -- Fiction; Mystery fiction